Information Technology and Applications : Proceedings of the 2014 International Conference on Information Technology and Applications (ITA2014), Xi'an, China, 8-9 August 2014 /: Proceedings of the 2014 International Conference on Information Technology and Applications (ITA2014), Xi'an, China, 8-9 August 2014. ([2015]) - Unknown
No abstract available